Discovering History in a Digital World: The Texas Story Project. (2nd July 2016) - Munns, David
ABSTRACT: New digital tools and technologies create an opportunity for history museums to personalize visitor experiences, reach new audiences, and increase their relevancy by including visitors' historical narratives in museum content and programming. By adapting to the shift in social narrative prompted by digital media advancements, museums are discovering opportunities for engaging an expanded audience – rethinking what a visitor is, what defines a museum visit, how history is interpreted, and the breadth and depth of the community they serve – as evidenced in the Bullock Texas State History Museum's "Texas Story Project."